1988
DOI: 10.1037/0022-3514.55.5.795
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors in nonincarcerated sexually aggressive men.

Abstract: Research on convicted rapists has demonstrated the importance of several key motivational factors in male sexual aggression. In particular, anger at women and the need to dominate or control them have been repeatedly implicated. Although anger and power have also been shown to be important in understanding college men who report sexually aggressive behavior, there has been little research on what underlies these motives. This research combined questions assessing these underlying motivational factors, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 22 publications
6
111
0
Order By: Relevance
“…Rapaport and Burkhart (1984) found that college men's coercive sex scores were negatively correlated with measures of socialization and responsibility. Impulsivity and aggressiveness are positively related to sexual assault perpetration among college men (Greendlinger & Byrne, 1987;Lisak & Roth, 1988;Petty & Dawson, 1989).…”
Section: Perpetrators' Personality Characteristicsmentioning
confidence: 98%
“…Rapaport and Burkhart (1984) found that college men's coercive sex scores were negatively correlated with measures of socialization and responsibility. Impulsivity and aggressiveness are positively related to sexual assault perpetration among college men (Greendlinger & Byrne, 1987;Lisak & Roth, 1988;Petty & Dawson, 1989).…”
Section: Perpetrators' Personality Characteristicsmentioning
confidence: 98%
“…A reliability a coefficient of .89 for college men and 1-week test-retest reliability with a mean item agreement of 93% was reported by Koss and Gidycz (1985) for the SES. Lisak and Roth (1988) conducted a small-scale assessment of validity for the SEQ using posttest interviews and reported "a greater degree of validity . .…”
Section: Methodsmentioning
confidence: 99%
“…A history of self-reported SV perpetration against a female victim was assessed using a 12-item version (0 [never], 4 [often]) of the Sexual Experiences Questionnaire (SEQ; Lisak & Roth, 1988). The SEQ is a short-form version of the Sexual Experiences Survey (SES; Koss & Gidycz, 1985;Koss & Oros, 1982), which has been used extensively in the previous research on sexual perpetration.…”
Section: Methodsmentioning
confidence: 99%
“…These factors can be conceived of in two ways: the first referring to external or situational factors that disinhibit arousal of an individual in the moment, and the second referring to personal dispositions that reduce the effects of social constraints against sexual aggression (Lisak & Roth, 1988). Investigations of disinhibiting personal characteristics suggest that antisocial and psychopathic tendencies, supportive attitudes and beliefs in rape myths, and hostility toward women might facilitate sexual aggression (Abbey & McAuslan, 2004;Burt & Albin, 1982;Lalumière & Quinsey, 1996;Quinsey, Book, & Lalumière, 2001;Senn et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations into the personal characteristics of men who engage in sexual aggression suggest an association with having an angry disposition toward women (Lisak & Roth, 1988). But more than having an angry disposition in general, does experiencing anger have an effect on sexual aggression?…”
Section: Angermentioning
confidence: 99%